Modeling of Scattering the Electromagnetic Pulses by High Voltage Converters - Kannan, R. (Institute of Electrical and Electronics Engineers Inc., 2021)
In this paper Electro Magnetic Pulse (EMP) which is used to destroy the electrical and electronic equipment operation in defence is proposed. The EMP is a small burst of electro magnetism. It's a highly disruptive signal which has a property of high magnetic transients. A nuclear weapon actually generate an EMP regardless of altitude when detonated, however the effects of the EMP only becomes useful at high altitudes where the energy released is not so rapidly dispersed as a surface discharged. Temporary or permanent damages may occur to unshielded electronics devices due to EMP. This EMP also causes power failure in all unshielded devices and disabling them. The only way to suppress the EMP is to use faraday cage, but faraday cage alone has some capacity. EMP operated at 400 kV, 10-12 MHz, which can detect and deactivate electronics devices over a range of 10-15 meters, is designed for defence purpose. Â© 2021 IEEE.